Lightweight high-strength hollow SiO2 aerogel composite board and preparation method thereof
By using methyl orthosilicate/methanol system and water-soluble powder modifier in SiO2 aerogel materials, and combining ultrasonic technology to form a hollow structure, the problem of insufficient mechanical properties of SiO2 aerogel materials is solved and light quality is achieved , Preparation of hollow SiO2 aerogel composite plate with high strength and high pass rate.
Patent Information
- Application Number
- CN202411525971.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The mechanical properties of existing SiO2 aerogel materials are poor, which limits the industrial application of large-size transparent SiO2 aerogel composite glass.
Use methyl orthosilicate/methanol as the silica sol system, and use water-soluble micron-scale powder modifier and ultrasonic technology to form a suspension, molded by sol-gel method, and dissolve the wet gel under high-frequency ultrasonic wave. The powder modifier hollows the inside of it to produce a lightweight, high-strength, large-size hollow SiO2 aerogel plate.
It improves the mechanical properties of SiO2 aerogel materials, enhances the one-time molding pass rate of large-size aerogel products, realizes the characteristics of lightweight and high strength, and simplifies the preparation process, which is suitable for industrial production.
Smart Images

Figure CN119461389A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel composite material manufacturing, and in particular to a lightweight and high-strength hollow SiO2 aerogel composite plate and a preparation method thereof. Background Art
[0002] With the rapid development of my country's economy, my country's building energy consumption has become one of the three major energy consumers, along with industrial energy consumption and transportation energy consumption. Large-size transparent aerogel composite glass has attracted widespread attention at home and abroad as a disruptive thermal insulation product. However, due to the poor mechanical strength of aerogel materials, the industrial application of large-size transparent aerogel composite glass is greatly limited. Based on this, domestic and foreign scholars have improved the mechanical strength of aerogels by optimizing the type of silicon source and reaction conditions. For example, Shen Jun et al. used monomers such as vinyl trimethoxysilane and methyl vinyl dimethoxysilane to first use free radical polymerization and then hydrolysis, polycondensation, aging and drying to prepare flexible silicone aerogel composite materials, and showed high compressibility and bendability. On the other hand, the brittleness of the aerogel network structure is improved by doping other components to construct a flexible network skeleton, achieving an enhanced effect. For example, Nguyen BN et al. used di(3-trimethoxysilylpropyl)amine and triisocyanate-modified methyl trimethoxysilane to increase the branching degree of SiO2 aerogel and improve its compressive strength. Although the above methods can improve the mechanical properties of aerogel materials, the density of the final aerogel material increases, the aerogel is fragile during the drying process, the preparation process is complicated and the reaction conditions are relatively harsh, which is not suitable for industrial mass production and application. Therefore, how to improve the strength of aerogel materials while taking into account the lightweight of aerogel materials, the simplicity of preparation and the high product qualification rate is extremely important for the industrial application of large-size transparent aerogel composite glass, and is of great significance to my country's realization of the "dual carbon" goal. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a lightweight and high-strength hollow SiO2 aerogel composite plate and a preparation method thereof. The method can effectively solve the problem that the industrial application of large-size transparent SiO2 aerogel composite glass is limited due to the poor mechanical properties of existing SiO2 aerogel materials, and can improve the one-time molding pass rate of large-size aerogel products. The prepared SiO2 aerogel composite plate has a large-size hollow pore structure with good energy absorption effect, and is lightweight and high-strength.
[0004] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a lightweight and high-strength hollow SiO2 aerogel composite plate comprises the following steps: Step S1. Mix methyl orthosilicate and methanol in a mass ratio of 1: (3-9) and stir evenly, add 1 mol / L hydrochloric acid to adjust the pH to 3-4 (acidic), add a mixed solution of ammonium fluoride and water, mix evenly, and hydrolyze at 50-60°C for 2-6h to obtain silica sol. The mixed solution of ammonium fluoride and water is obtained by mixing and dissolving ammonium fluoride and water in a mass ratio of 0.005: (0.012-0.018).
[0005] Step S2. Take a water-soluble powder modifier and place it in the above-mentioned silica sol, and disperse it under low-frequency ultrasound to form a stable suspension. The powder modifier is any one or a combination of two of cyclodextrin (α-type, β-type, γ-type), polyvinyl alcohol, polyethylene glycol, starch magnesium aluminum silicate, lithium magnesium silicate, and sodium magnesium silicate, and the particle size range of the powder modifier is 0.3 to 2 μm. The mass ratio of the powder modifier to the silica sol is (0.001 to 0.02): 1. The frequency range of the low-frequency ultrasound is 15 to 33 KHz, and the ultrasound time is 30 min to 2 h.
[0006] Step S3. Place the above suspension in a mold, add a catalyst and stir evenly, and let it stand at 50-55°C for 5-15 minutes to obtain a wet gel. The catalyst is any one of ammonia water, potassium hydroxide, and tetramethylammonium hydroxide. The mass ratio of the catalyst to the suspension is (0.01-0.03):1.
[0007] Step S4. Place the wet gel in a mixture of water and methanol, and use high-frequency ultrasound to dissolve the powder modifier in the wet gel at 70-75°C, repeatedly replace the soaking liquid (the liquid soaking the wet gel) until the powder modifier in the wet gel is completely dissolved. In the mixture of water and methanol, the volume ratio of water to methanol is 1: (0.2-7). The frequency range of the high-frequency ultrasound is 50-60KHz, and the ultrasound time is 5-12h.
[0008] Step S5. After the wet gel becomes transparent, the wet gel is aged and dried in sequence to obtain the lightweight and high-strength hollow SiO2 aerogel composite plate. The methanol aging temperature range is 60-65°C, and the aging time range is 24-48h. The drying is carried out by supercritical CO2 drying, the supercritical CO2 drying pressure is 14MPa-15MPa, the drying temperature is 60°C-65°C, and the drying time is 7h-10h.
[0009] In addition, the present invention also discloses a lightweight and high-strength hollow SiO2 aerogel composite plate prepared by the method.
[0010] The present invention uses methyl orthosilicate / methanol as the silica sol system, uses water-soluble micron-sized powder as a modifier, uses low-frequency ultrasound to disperse the modifier in the silica sol to form a suspension, and uses a water / methanol mixture to dissolve the water-soluble powder inside the SiO2 wet gel under high-frequency ultrasound after forming by the sol-gel method to make the inside hollow, thereby obtaining a lightweight, high-strength large-sized hollow SiO2 aerogel plate. The obtained large-sized hollow SiO2 aerogel plate effectively solves the problem that the existing SiO2 aerogel material has poor mechanical properties, which limits the industrial application of large-sized transparent SiO2 aerogel composite glass. The present invention has the following advantages: (1) In the process of preparing hollow SiO2 aerogel composite boards, the large-sized hollow structure can absorb the impact pressure of supercritical CO2 drying on the aerogel material during the final drying, thereby reducing warping and cracking problems and improving the one-time molding qualification rate of large-sized aerogel products.
[0011] (2) The large-size hollow structure of the prepared hollow SiO2 aerogel composite plate has a strong energy absorption effect. Its strength is 2-4 times that of traditional SiO2 aerogel materials, which effectively improves the mechanical properties of SiO2 aerogel materials and contributes to the practical application of large-size aerogel composite glass in industrial life.
[0012] (3) The prepared hollow SiO2 aerogel composite board is lighter than the traditional SiO2 aerogel composite board.
[0013] (4) The entire production process is simple, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0015] Figure 1 This is a physical picture of the lightweight and high-strength hollow SiO2 aerogel composite plate prepared in Example 1 of the present invention.
[0016] Figure 2 This is a physical picture of the lightweight and high-strength hollow SiO2 aerogel composite plate prepared in Example 2 of the present invention.
[0017] Figure 3 This is a physical picture of the lightweight and high-strength hollow SiO2 aerogel composite plate prepared in Example 3 of the present invention.
[0018] Figure 4 This is a physical picture of the SiO2 aerogel composite plate prepared in the comparative example. DETAILED DESCRIPTION
[0019] The following is an explanation of the implementation of the present invention by specific specific embodiments. People familiar with the technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0020] This embodiment discloses a method for preparing a lightweight and high-strength hollow SiO2 aerogel composite plate, comprising the following steps: Take methyl orthosilicate and methanol in a mass ratio of 1:7 and mix them evenly, add 1mol / L hydrochloric acid to adjust the pH to 3-4 (acidic), add a mixture of ammonium fluoride and water, mix well, and hydrolyze at 55°C for 3h to obtain silica sol. Among them, the mixture of ammonium fluoride and water is obtained by mixing and dissolving ammonium fluoride and water in a mass ratio of 0.005:0.014. Take 0.01 parts of γ-cyclodextrin powder with a particle size of 0.5μm by weight and place it in 1 part of silica sol, disperse it under 25KHz ultrasound for 1.5h to form a stable suspension. Take 1 part of the suspension by weight and place it in a mold, add 0.005 parts of ammonia water and stir evenly, and then stand at 55°C for 13min to obtain a wet gel. The wet gel was placed in a mixture of water and methanol (the volume ratio of water to methanol in the mixture was 1:5), and the powder modifier in the wet gel was dissolved using 55KHz ultrasound at 70°C. During the ultrasonic dissolution, the immersion liquid was replaced 4 times, and the ultrasonic dissolution time was 8 hours until the powder modifier in the wet gel was completely dissolved. After the wet gel became transparent, it was aged with methanol at 65°C for 36 hours, and then supercritical CO2 drying was performed, wherein the drying pressure was 15MPa, the drying temperature was 65°C, and the drying time was 8 hours, and finally a lightweight and high-strength hollow SiO2 aerogel composite plate was obtained. Example 2
[0021] This embodiment discloses a method for preparing a lightweight and high-strength hollow SiO2 aerogel composite plate, comprising the following steps: Take methyl orthosilicate and methanol in a mass ratio of 1:7 and mix them evenly, add 1mol / L hydrochloric acid to adjust the pH to 3-4 (acidic), add a mixture of ammonium fluoride and water, mix well, and hydrolyze at 55°C for 3h to obtain silica sol. Among them, the mixture of ammonium fluoride and water is obtained by mixing and dissolving ammonium fluoride and water in a mass ratio of 0.005:0.014. Take 0.01 parts of polyethylene glycol with a particle size of 0.5μm by weight and place it in 1 part of silica sol, disperse it under 25KHz ultrasound for 1.5h to form a stable suspension. Take 1 part of the suspension by weight and place it in a mold, add 0.005 parts of ammonia water and stir evenly, and then stand at 55°C for 13min to obtain a wet gel. The wet gel was placed in a mixture of water and methanol (the volume ratio of water to methanol in the mixture was 1:5), and the powder modifier in the wet gel was dissolved using 55KHz ultrasound at 70°C. During the ultrasonic dissolution, the immersion liquid was replaced 4 times, and the ultrasonic dissolution time was 8 hours until the powder modifier in the wet gel was completely dissolved. After the wet gel became transparent, it was aged with methanol at 65°C for 36 hours, and then supercritical CO2 drying was performed, wherein the drying pressure was 15MPa, the drying temperature was 65°C, and the drying time was 8 hours, and finally a lightweight and high-strength hollow SiO2 aerogel composite plate was obtained. Example 3
[0022] Take methyl orthosilicate and methanol in a mass ratio of 1:7 and mix them evenly, add 1mol / L hydrochloric acid to adjust the pH to 3-4 (acidic), add a mixture of ammonium fluoride and water, mix well, and hydrolyze at 55°C for 3h to obtain silica sol. Among them, the mixture of ammonium fluoride and water is obtained by mixing and dissolving ammonium fluoride and water in a mass ratio of 0.005:0.014. Take 0.01 parts of magnesium aluminum silicate with a particle size of 0.5μm by weight and place it in 1 part of silica sol, disperse it under 25KHz ultrasound for 1.5h to form a stable suspension. Take 1 part of the suspension by weight and place it in a mold, add 0.005 parts of ammonia water and stir evenly, and then stand at 55°C for 13min to obtain a wet gel. The wet gel was placed in a mixture of water and methanol (the volume ratio of water to methanol in the mixture was 1:5), and the powder modifier in the wet gel was dissolved using 55KHz ultrasound at 70°C. During the ultrasonic dissolution, the immersion liquid was replaced 4 times, and the ultrasonic dissolution time was 8 hours until the powder modifier in the wet gel was completely dissolved. After the wet gel became transparent, it was aged with methanol at 65°C for 36 hours, and then supercritical CO2 drying was performed, wherein the drying pressure was 15MPa, the drying temperature was 65°C, and the drying time was 8 hours, and finally a lightweight and high-strength hollow SiO2 aerogel composite plate was obtained. Comparative Example
[0023] This comparative example adopts the existing method for preparing SiO2 aerogel composite board.
[0024] Take methyl orthosilicate and methanol in a mass ratio of 1:7 and mix them evenly. After adding 1 mol / L hydrochloric acid to adjust the pH to 3-4 (acidic), add a mixture of ammonium fluoride and water and mix well, and hydrolyze at 55°C for 3h to obtain silica sol. Among them, the mixture of ammonium fluoride and water is obtained by mixing and dissolving ammonium fluoride and water in a mass ratio of 0.005:0.014. Take 1 part of silica sol liquid by weight and place it in a mold, add 0.005 parts of ammonia water and stir evenly, and then stand at 55°C for 13min to react to obtain a wet gel. After aging it with methanol at 65°C for 36h, it is dried by supercritical CO2, where the drying pressure is 15MPa, the drying temperature is 65°C, and the drying time is 8h, and finally a SiO2 aerogel composite plate is obtained.
[0025] The SiO2 aerogel composite plates were divided into four groups, each group had 20 SiO2 aerogel composite plates, and were numbered as Group A, Group B, Group C, and Group D, wherein the SiO2 aerogel composite plates in Group A were prepared by the method described in Example 1, the SiO2 aerogel composite plates in Group B were prepared by the method described in Example 2, the SiO2 aerogel composite plates in Group C were prepared by the method described in Example 3, and the SiO2 aerogel composite plates in Group D were prepared by the method described in the comparative example. The density, compression strength, and impact strength of the SiO2 aerogel composite plates in each group were tested, and the records were compared. The comparison results are shown in Table 1.
[0026] Table 1 Performance test comparison of each group of SiO2 aerogel composite panels
[0027] Combination Figures 1 to 4 As shown in Table 1, the analysis is as follows: (1) The hollow SiO2 aerogel composite plate prepared by the method of the present invention (Examples 1-3) is significantly superior to the SiO2 aerogel composite plate prepared by conventional technical means (Comparative Example) in terms of density, compression strength and impact strength.
[0028] (2) By comparing the situations of Group A, Group B and Group C, it can be seen that the hollow SiO2 aerogel composite board of Group B is significantly better than those of Group A and Group C in terms of density, compressive strength and impact strength. It can be concluded that when the types of powder modifiers added are different, the prepared hollow SiO2 aerogel composite boards will have obvious differences in performance.
[0029] Other aspects of the present invention that are not described in detail are all conventional techniques known to those skilled in the art.
[0030] It should be noted that the terms "comprises", "includes" or any other variations are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0031] The protection scope of the present invention is not limited to the technical solutions disclosed in the specific implementation methods. Any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board, characterized in that: The following steps are involved: Step S1. Mix methyl orthosilicate and methanol, adjust the pH to acidic, add a mixture of ammonium fluoride and water, mix well, and hydrolyze to obtain silica sol; Step S2. taking a water-soluble powder modifier and placing it in silica sol, and dispersing it under ultrasound to form a stable suspension; Step S3. Place the suspension in a mold, add a catalyst, stir evenly, and allow to react to obtain a wet gel; Step S4. Place the wet gel in a mixture of water and methanol, and use ultrasound to dissolve the powder modifier in the wet gel, repeatedly replacing the soaking liquid until the powder modifier in the wet gel is completely dissolved; Step S5. After the wet gel becomes transparent, the wet gel is aged and dried in sequence to obtain the lightweight and high-strength hollow SiO2 aerogel composite board.
2. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: The powder modifier is any one of cyclodextrin (α-type, β-type, γ-type), polyvinyl alcohol, polyethylene glycol, starch magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, or a combination of two thereof.
3. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: The particle size of the powder modifier is in the range of 0.5 to 2 μm.
4. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: The ultrasonic wave used in step S2 is a low-frequency ultrasonic wave, which ranges from 15 to 33 KHz, and the ultrasonic wave time is 30 minutes to 2 hours.
5. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: In step S2, the mass ratio of the powder modifier to the silica sol is (0.001-0.02):
1.
6. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: In step S3, the catalyst is any one of ammonia water, potassium hydroxide, and tetramethylammonium hydroxide; the mass ratio of the catalyst to the suspension is (0.001-0.03):
1.
7. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: In the mixed solution of water and methanol in step S4, the volume ratio of water to methanol is 1:(0.2-5).
8. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: The ultrasonic dissolution temperature range of step S4 is 70-75°C.
9. The method for preparing a lightweight and high-strength hollow SiO2 aerogel composite board according to claim 1, characterized in that: The ultrasonic wave in step S4 is a high-frequency ultrasonic wave, which ranges from 50 to 60 KHz, and the ultrasonic wave time is 5 to 12 hours.
10. A lightweight and high-strength hollow SiO2 aerogel composite board, characterized in that: The lightweight and high-strength hollow SiO2 aerogel composite board is made by the preparation method of any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of aluminum-silicon-magnesium ternary aerogel
CN120325197A
A method for preparing aluminum-silicon-magnesium ternary aerogel
CN120325197B